VH Replacement Footprint Analyzer-I, a Java-Based Computer Program for Analyses of Immunoglobulin Heavy Chain Genes and Potential VH Replacement Products in Human and Mouse - Huang, Lin; Lange, Miles D.; Zhang, Zhixin (Frontiers in Immunology, 2014)
VH replacement occurs through RAG-mediated secondary recombination between a rearranged VH gene and an upstream unrearranged VH gene. Due to the location of the cryptic recombination signal sequence (cRSS, TACTGTG) at the 3′ end of VH gene coding region, a short stretch of nucleotides from the previous rearranged VH gene can be retained in the newly formed VH–DH junction as a “footprint” of VH replacement. Such footprints can be used as markers to identify Ig heavy chain (IgH) genes potentially generated through VH replacement. To explore the contribution of VH replacement products to the antibody repertoire, we developed a Java-based computer program, VH replacement footprint analyzer-I (VHRFA-I), to analyze published or newly obtained IgH genes from human or mouse. The VHRFA-1 program has multiple functional modules: it first uses service provided by the IMGT/V-QUEST program to assign potential VH, DH, and JH germline genes; then, it searches for VH replacement footprint motifs within the VH–DH junction (N1) regions of IgH gene sequences to identify potential VH replacement products; it can also analyze the frequencies of VH replacement products in correlation with publications, keywords, or VH, DH, and JH gene usages, and mutation status; it can further analyze the amino acid usages encoded by the identified VH replacement footprints. In summary, this program provides a useful computation tool for exploring the biological significance of VH replacement products in human and mouse.